The economic impact of prenatal varicella immunity among pregnant women in Alberta. Issue 4 (23rd January 2017) - Passi, Amrit; Plitt, Sabrina S.; Lai, Florence Y.; Simmonds, Kimberley; Charlton, Carmen L.
Highlights: Vaccinated women had lower VZV antibody levels than women who had natural infection. VZV antibodies do not appear to be well maintained following postpartum vaccination. 40.9% of all prenatal varicella IgG tested were found to be redundant. Abstract: In light of the changing epidemiology of varicella, we sought to examine varicella antibody levels in the prenatal population in the Canadian province of Alberta. All prenatal varicella screening tests performed between August 1, 2002 and February 2, 2014 (454, 592) were included in this study. Test results, demographics and vaccination status were examined to identify varicella seroprevalence and correlates for being seronegative. An overall seroprevalence for varicella of 95.8% was found across all pregnancy screenings. Significant independent correlates of seronegativity included younger age (AOR: 4.72 (95% CI: 3.87–5.77) for <20 years of age vs. >40 years of age) and having immigrated to Alberta from Africa or Asia (AOR: 4.55 (95% CI: 4.10–5.05) and AOR: 5.83 (95%CI; 5.48–6.19), respectively). Women who were initially seronegative for varicella antibodies and who received both postnatal vaccination and post-vaccination prenatal screening (2566) were examined to assess seroconversion. 66.3% of women who were tested up to six months post-vaccination were seropositive, however only 36.9% of women tested after 36 months were seropositive. Finally, 40.9% of all prenatal varicella specimens tested were deemed redundant, i.e. women had either a history of (1) ⩾2 doses of varicella vaccine, (2) varicella infection, or (3) a previous positive varicella serology. Eliminating this redundant screening could provide an estimated 96, 000 in savings annually in laboratory and Public Health follow-up costs alone. As the number of women with vaccine-derived immunity through universal childhood vaccination increase in the prenatal population, screening methods may need to adapt to ensure varicella immunity is accurately conducted and assessed.